Penguatan Kompetensi Manajerial Pengurus Yayasan Tk Muslimat Khodijah 157 Rogojampi Melalui Pelatihan Manajemen Lembaga - Saqofa Nabilah Aini (LPPI UMN AL WASHLIYAH, 2026)
This community service program aimed to enhance the managerial capacity and institutional governance of TK Muslimat Khodijah 157 Rogojampi through a series of intensive training sessions. The first session focused on strengthening managerial competence and institutional governance, while the second session emphasized leadership development, problem-solving and decision-making skills, as well as the implementation of effective organizational practices. The program evaluation employed the CIPP (Context, Input, Process, Product) model to comprehensively assess the quality of implementation.The evaluation results indicate that the context and input components met all criteria related to planning and the provision of relevant resources. The process component proceeded according to the training design, characterized by active participation, interactive facilitation methods, and a supportive learning environment. In terms of product, participants demonstrated improved understanding and skills in institutional management, administrative structuring, and the application of more orderly and professional governance practices. Overall, the program successfully contributed to strengthening institutional quality and improving the competencies of the teaching staff. Moving forward, sustained mentoring and periodic monitoring are recommended to ensure the long-term implementation and integration of these improvements within the school environment.